Amoebic granulomatous encephalitis in an immunocompetent patient (Revista Venezolana de Salud Pública, 2018)
Granulomatous amoebic encephalitis is an infrequent clinical entity, usually present in immunocompromised persons,where the few cases reported in the literature are due to infections by free-living amoebas present throughout the world,standing out as the most common agents, the Acanthamoeba sp. and Balamuthia mandrillaris. It is characterized by an insidious clinical course,that can be prolonged, but equally fatal. The clinic corresponds to that of intracerebral space occupying lesions, withseizures and focal deficits such as hemiparesis and cranial nerve lesions. Alterations of the sensorium, headache and neck stiffness areequally common, however, fever is usually sporadic and low grade. Occasionally there are pictures of pneumonitis,kidney or liver failure and sepsis.
Keywords: Amoebic granulomatous encephalitis; immunocompetent patient; free-living amoebas.